Ustrój państwa polsko-litewskiego w latach 1573-1581 : ustrój mieszany, czy demokracja szlachecka? - Chmielecki, Damian (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The purpose of this article is to reconcile existing research on the political system of the Polish-Lithuanian Commonwealth between 1573 and 1581. The article presents two concepts defining the structure of the Polish-Lithuanian Commonwealth: as mixed regime (monarchia mixta) or gentry-democracy. The first part of the paper focuses on claims made by historians of law who - harking back to the 16th century Polish political thought- are in favour of classifying the political system of the Polish-Lithuanian Commonwealth as mixed regime. Next, views of ancient and Renaissance thinkers (who have had a direct impact on the Polish thinkers of the 16th century) on mixed regime are presented. The last part of the article deals with claims of historians who believe that the political system of the Polish-Lithuanian Commonwealth should be best defined as gentry-democracy. The aim of the article is to objectively present both concepts
Keywords: ustrój mieszany; monarchia mixta; demokracja szlachecka; ustrój państwa; Polska; Litwa; 16 w.